Programming languages : concepts and constructs - Sethi, Ravi. (Reading, Mass. : Addison-Wesley, 1996)
Programming Languages: Concepts and Constructs, Second Edition retains the "character" of the original, emphasizing concepts and how they work together. This classic book has been thoroughly revised to provide readable coverage of the major programming paradigms. Dr. Sethi's treatment of the core concepts of imperative programming in languages like Pascal and C flows smoothly into object-oriented programming in C++ and Smalltalk.
The charm of functional languages is illustrated by programs in Standard ML and the Scheme dialect of Lisp. Logic programming is introduced using Prolog.
. Novices, who have been introduced to programming in some language, will learn from this book how related concepts work together while designers and implementers will be exposed to the major programming paradigms.
Includes bibliographical references and index.
Keywords: Programming languages (Electronic computers)